1984
DOI: 10.1159/000206604
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Superoxide Anion Production in Neutrophils from Multitransfused β-Thalassemia Patients: Correlation with Ferritin Levels and Liver Damage

Abstract: Superoxide anion production in resting and PMA- or zymosan-stimulated neutrophils was evaluated in 21 β-thalassemia patients. The results were correlated with ferritin values, hepatitis B virus serum markers, liver pathology, immunoglobulin levels and T-cell subsets. Superoxide anion generation from resting or PMA-stimulated neutrophils was significantly higher in patients than in controls. On the contrary, zymosan-stimulated neutrophils showed reduced superoxide anion production. Increased superoxide anion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…Positive sera stained at least HTLV-III infection. In previous papers we have reported a number of immunological changes in ß-thalassemics which were corre lated to splenectomy, iron overload, and hepatitis B virus infection [7,10]. In partic ular, we observed that inverted OKT4/OKT8 ratio and decreased mitogen responsiveness were present in patients who had started transfusion therapy very early in life [5], Analogously, it is possible that in hemophiliacs factor VIII concentrate modi fies the immunological status independently of HTLV-III infection [11], A careful follow up of the patients with immunological mod ifications will answer the question whether a preexisting immunological defect helps HTLV-III infection to take root [12],…”
Section: Antibodies To Htlv-iiimentioning
confidence: 99%
“…Positive sera stained at least HTLV-III infection. In previous papers we have reported a number of immunological changes in ß-thalassemics which were corre lated to splenectomy, iron overload, and hepatitis B virus infection [7,10]. In partic ular, we observed that inverted OKT4/OKT8 ratio and decreased mitogen responsiveness were present in patients who had started transfusion therapy very early in life [5], Analogously, it is possible that in hemophiliacs factor VIII concentrate modi fies the immunological status independently of HTLV-III infection [11], A careful follow up of the patients with immunological mod ifications will answer the question whether a preexisting immunological defect helps HTLV-III infection to take root [12],…”
Section: Antibodies To Htlv-iiimentioning
confidence: 99%
“…Transfusions lead to iron overload and also to immune derangements, both of which exert a negative effect on the functional integrity of the immune system in multitransfused patients with thalassaemia. There are already a large number of reports describing immune abnormalities in thalassaemia, namely defective function of polymorphonuclear neutrophils and monocytes [2,3], decrease of CD4 + cells and increase of CD8 + cells [4][5][6], diminished mitogen responses [5] and low natural killer (NK) cell activity [7,8]. These and probably other undetected abnormalities may explain the tendency for severe or unusual infections.…”
Section: Introductionmentioning
confidence: 99%
“…In multitransfused TM patients, the increase of reactive iron may induce an increase in oxygen free radicals generation [27], Different authors have ob served that in resting and stimulated phagocytes from multitransfused thalassemic patients, the production of superoxide anion is significantly enhanced, associated with serum ferritin levels [28], The impairment of phago lysosomal fusion of monocytes from TM patients could then be due to the peroxidation of membranes caused by oxygen free radicals. Probably, a slight increase of serum ferritin levels is enough to alter phagolysosomal fusion, explaining the lack of association between the grade of monocyte phagolysosomal dysfunction and ferritin levels.…”
Section: Discussionmentioning
confidence: 99%